MAIN GOALS OF PSYCHOLOGICAL REHABILITATION OF MILITARY SERVICEMEN IN THE POLTAVA REGION UNDER THE PRESENT CONDITIONS - Havlovskyi, O.D. (World of Medicine and Biology, 2020)
The outbreak of the war in the East of Ukraine has created new challenges for the psychological rehabilitation system. The purpose of the work was to analyse the main goals of psychological rehabilitation of military servicemen in the Poltava region in present conditions. The reports of the Rehabilitation Department of the Public Institution “Kremenchug Regional Clinical Hospital for Veterans of War” of the Poltava Regional Council were analysed for the 2014-2018. During 2014 and 2015 medical assistance to servicemen was provided only on an inpatient basis. Since 2016, it has become necessary to consult military personnel on an outpatient basis (2016 – 473 people (51.8%), 2017 – 570 people (48.3%), 2018 – 745 people (47.6%)) The highest percentage of treated military personnel was diagnosed with neurotic, stress-related and somatoform disorders, respectively in 2016 – 58.6%, in 2017 – 59.3%, and in 2018 – 56.7%. The presence among the military personnel of anti-terrorist operation / united forces operation of a constant increase in the number of patients with signs of impaired adaptation requires the earliest possible start of psychological rehabilitation.